Chiang Yee : the silent traveller from the East : a cultural biography - Zheng, Da, 1953- (Rutgers University Press, 2010)
This is the true story of Chiang Yee, a renowned writer, artist, and worldwide traveler, best known for the Silent Traveller series̮stories of England, the United States, Ireland, France, Japan, and Australia̮all written in his humorous, delightfully refreshing, and enlightening literary style. This biography is more than a recounting of extraordinary accomplishments. Da Zheng uncovers Yee's encounters with racial exclusion and immigration laws, displacement, exile, and the pain and losses he endured hidden behind a popular public image.